2023
DOI: 10.3390/jcm12082878
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Tracheal Oxygen Tension and Diffusion Ratio When Choosing High-Flow Oxygen Therapy or CPAP for the Treatment of Hypoxemic Respiratory Failure: Insights from Ex Vivo Physiologic Modelling

Abstract: This article is a review of the physiological and technological processes underpinning high-flow nasal therapy with oxygen (HFNT or HFOT) for the treatment of hypoxemic respiratory failure. A mathematical model was carefully built to represent the relationships between the settings on the HFNT device and the resultant diffusion of oxygen into hypoxemic, arterial blood. The analysis was used to recommend a strategy for setting the flow rate at or above the patient’s peak inspiratory flow when HFNT is used with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In particular, Vega Pittao et al [ 2 ] described the mechanisms of HFNC in fields that have still not been fully investigated like chronic hypercapnic respiratory failure, while in a sophisticated ex vivo modelling, Truschel and Polkey [ 3 ] demonstrated that HFNC is as effective for promoting oxygen diffusion as CPAP when oxygen is entrained at the mask and is superior to CPAP where oxygen is entrained at the back of the device. Specifically, the benefit from alveolar expansion from CPAP pressure or increased end expiratory lung volume (EELV) provides no significant benefit to oxygenation in non-atelectatic lungs.…”
mentioning
confidence: 99%
“…In particular, Vega Pittao et al [ 2 ] described the mechanisms of HFNC in fields that have still not been fully investigated like chronic hypercapnic respiratory failure, while in a sophisticated ex vivo modelling, Truschel and Polkey [ 3 ] demonstrated that HFNC is as effective for promoting oxygen diffusion as CPAP when oxygen is entrained at the mask and is superior to CPAP where oxygen is entrained at the back of the device. Specifically, the benefit from alveolar expansion from CPAP pressure or increased end expiratory lung volume (EELV) provides no significant benefit to oxygenation in non-atelectatic lungs.…”
mentioning
confidence: 99%